DEVELOPMENT OF THE THIRST DISCOMFORT SCALE: A VALIDITY AND RELIABILITY STUDY - Ciftci, Bahar; Yildiz, Guezel Nur; Avsar, Guelcin; Koese, Sema; Aydin, Esra; Dogan, Sevgi; Celik, Seymanur (Amer Assoc Critical Care Nurses, 2023)
Background Thirst is a sensation associated with a dry mouth and the desire or craving to drink water. Surgical patients are among those hospitalized individuals who are at high risk of developing both osmotic and hypovo-lemic thirst. Objectives To develop a new measurement tool for eval-uating the thirst-related discomfort of surgical patients and to assess its validity and reliability. Methods The study population consisted of patients admitted to the surgical clinics of a research hospital in Turkey between January and March 2022. The new mea-surement tool was developed in several stages: a pilot implementation phase with 51 patients and the main implementation phase with 198 patients. Data were col-lected by means of face-to-face interviews with patients. Exploratory factor and confirmatory factor analyses were performed using IBM SPSS Statistics, version 22, and IBM SPSS Amos. Results The final Thirst Discomfort Scale consisted of 12 items in 3 subdimensions. The Cronbach _ values of the scale subdimensions ranged from 0.787 to 0.848, and the Cronbach _ value for the scale as a whole was 0.886. The scale explained 66.237% of the total variance of the data. Conclusion The Thirst Discomfort Scale consisting of 12 items and 3 subdimensions is a valid and reliable mea-surement tool for evaluating thirst-related discomfort of surgical patients. (American Journal of Critical Care. 2023;32:176-183)
Keywords: Dry Mouth; Distress Scale; Intervention